Genetic Diversity and Population Structure of Sorghum [Sorghum Bicolor (L.) Moench] Accessions as Revealed by Single Nucleotide Polymorphism Markers - Enyew, Muluken; Feyissa, Tileye; Carlsson, Anders S.; Tesfaye, Kassahun; Hammenhag, Cecilia; Geleta, Mulatu (Frontiers in Plant Science, 2022)
Ethiopia is a center of origin for sorghum (Sorghum bicolor), where the distinct agro-ecological zones significantly contributed to the crop’s genetic diversity. A large number of sorghum landrace accessions has been conserved ex-situ. Molecular characterization of this diverse germplasm can contribute to its efficient conservation and utilization in the breeding programs. This study aimed to investigate the genetic diversity of Ethiopian sorghum using gene-based single nucleotide polymorphism (SNP) markers. In total, 359 individuals representing 24 landrace accessions were genotyped using 3001 SNP markers. The SNP markers had moderately high polymorphism information content (PIC = 0.24) and gene diversity (H = 0.29), on average. This study revealed 48 SNP loci that were significantly deviated from Hardy-Weinberg equilibrium with excess heterozygosity and 13 loci presumed to be under selection (P < 0.01). The Analysis of molecular variance (AMOVA) determined that 35.5% of the total variation occurred within and 64.5% among accessions. Similarly, significant differentiations were observed among geographic regions and peduncle shape-based groups. In the latter case, accessions with bent peduncles had higher genetic variation than those with erect peduncles. More alleles that are private were found in eastern region than in other regions of the country, suggesting good in-situ conservation status in the east. Cluster, principal coordinate and STRUCTURE analyses revealed distinct accession-clusters. Hence, crossbreeding genotypes from different clusters and evaluating their progenies for desirable traits is advantageous. The exceptionally high heterozygosity observed in accession SB4 and SB21 from western geographic region is an intriguing finding of this study, which merits further investigation.